Industrialisation and Chinese big business in colonial Singapore, Malaya, and China: the transnational enterprises of Lim Peng Siang (1904–41) - Goh, Jeremy (2023)
While most studies of industrialisation and modernisation in Singapore have focused on the post-1960 period and the role of the new nation-state, multinational corporations, and government-linked companies, Lim Peng Siang's business career shows that these processes and engagements were already under way before the Second World War. This study seeks to foreground the dynamics of industrialisation and modernisation in the historiography of Chinese business in colonial Singapore, Malaya, and Southeast Asia through examining Lim's business career. It shows how the projects of industrialisation and modernisation that Lim and his contemporaries embodied extended beyond business and the economy, and were entangled in broader cultural, sociopolitical, and urban forces and developments in Singapore and other parts of colonial Southeast Asia, maritime Asia, and the world-at-large between the late nineteenth and early twentieth centuries. His experiences highlight the pitfalls of assuming a simple traditional–modern dichotomy, and any essentialistic and ethnic constructions of culture, and the discourses surrounding business strategy, behaviour, and thought.